UJI AKTIVITAS ENZIM LIPASE PADA FRAKSI SKIM SANTAN TERHIDROLISIS - moh su'i; Enny Sumaryati; Frida Dwi Anggraeni; Aghfariza Indriyani (Universitas Tribhuwana Tunggadewi, 2023)
Fresh coconut milk (not hydrolyzed) contains lipase enzymes. If coconut milk is hydrolyzed using lipase enzymes, it will produce free fatty acids, lauric acid, and monoglycerides (monolaurin), which have anti-bacterial and anti-viral activities. Besides that, hydrolyzed coconut milk can produce diglycerides which function as emulsifiers. During the hydrolysis process, it's a possibility of damage to the lipase enzyme due to the activity of the protease enzyme in coconut milk. The aim of this study is to examine the activity of the lipase enzyme in coconut milk which is hydrolyzed. The research used two factors, namely the first factor was the hydrolysis time (0, 24, and 48 hours) and the second factor was the incubation temperature (40 C and 55 C) which were arranged factorially. The study was repeated three times and used a randomized block design (RBD). The hydrolyzed fraction in the form of skim was tested for lipase enzyme activity, free fatty acid content, and yield. The results showed that coconut milk which was hydrolyzed for 2 days at 40 oC and 55 oC still contained the lipase enzyme with an activity of 3.49 to 9.40 units/ml. Large fatty acid levels ranged from 0.32 m mol/ml to 0.72 m mol/ml..